Synthesis of 4-hydroxy-3-methoxybenzaldehyde (Vanillin) Derivatives and Pharmacophore Modelling for Antimicrobial Agents Staphylococcus aureus (S.aureus) - Nur Sabrina, Mohd. Raime (Universiti Malaysia Sarawak (UNIMAS), 2015)
Staph infections and its complications have increased rapidly in this recent year due to the resistance of S.aureus strains to the current antibiotics. Currently there is no potent vaccine available to against S.aureus since the bacteria are so widespread and will cause so many different diseases.In this study, vanillin was used as the starting material to synthesize a new drug since vanillin show their properties for antimicrobial agent. Pharmacophore modelling was a new approach to search for potential antimicrobial agents with 9 vanillin derivatives were proposed as a test set (synthesized compound). Enoyl-ACP reductase (saFabI) was selected from Protein Data Bank website as target compound and their 3D structure was generated in LigandScout 3.1 for structure-based pharmacophore. The target compound and test set were merged to determine their interactions between both compounds. The vanillin derivatives were synthesized via Schiff base reaction. The characterization of the synthesized compounds was determined by using Fourier Transform Infra-Red and Nuclear Magnetic Resonance (1 H and 13C NMR). Biological evaluation was conducted using Brine Shrimp lethality test for cytotoxicity. The antimicrobial test, Kirby Bauer test was also conducted. The pharmacophore modelling showed that 2-methoxy-4-[(Z)- (phenylimino)methyl]phenol (6) from the reaction of vanillin and aniline was the highest number of interaction to DJUS1257 active site. Biological evaluation showed that the compound was cytotoxic and the antimicrobial assay also showed that compound (6) has antimicrobial property which can inhibit the growth of S.aureus. Therefore, compound (6) was selected as lead compound to against the staph infection.